Determination of Protein Concentration Using Bradford Microplate Protein Quantification Assay - Rouhollah Valipour Nouroozi; Moulood Valipour Noroozi; Masoumeh Ahmadizadeh (Disease and Diagnosis, 2015)
Background: Bradford protein assay is popular due to its ease of performance and relative sensitivity. Many researchers and laboratories in Iran use standard assay of Bradford by cuvette. No commercial kit was available for Bradford microplate assay in Iran. Meanwhile, imported Bradford commercial kits are very expensive and have a long delivery time in Iran. Till now no study or document on Bradford microplate protein quantification assay was reported in Iran, so this study aimed to design and carried out this assay. Methods: In the current study, antigen B of hydatid cyst fluid was used as sample and the assay was performed in microplate wells. The absorbance values were measured at 595 nm and standard curve was generated by Microsoft Office Excel software. The protein concentration of sample was calculated using the equation of the standard curve. Results: Average protein concentration of the sample was 1175 ;mug/ml. The total time needed for reading of absorbance was two minutes approximately. Conclusion: Bradford microplate protein assay is a fast and suitable method. This method could be replacing the time consuming method with cuvette. In addition, if this assay produces as a low price kit it could have many benefits for students and laboratories that need to determine protein concentration by Bradford assay.